A study on the behaviour of the residents at Felda Soeharto regarding solid waste separation - Mohamed Alli, Nur Anis; Roslinda Ali; Abdullah, Nor Maizzaty (Progress in Engineering Application and Technology, 2021)
The increasing amount of solid waste generation is becoming a global concern that is causing many problems to the environment and its living things.Among the problems due to the increasing of solid waste to human health include the low birth weight and cancers. The problem of solid waste also endangers the ecosystems of animals and plants and pose them to the threat of extinction. One of the measures that can be taken to reduce the amount of solid waste generation is by practicing the 3R concept. Therefore, a study was conducted to investigate on the behaviour of the residents staying at Felda Soeharto towards waste separation. The data collection is carried out in 2 stages: i) Part 1: Questionnaire survey; and ii) Part 2: Experimental awareness campaign. For Part 1, a self-administered questionnaire was distributed to the residents at Felda Soeharto to evaluate their perception in practicing the 3R concept in their daily life activities. The results will be analysed using SPSS software. In Part 2 of the data collection, an experimental campaign on waste cooking oil (WCO) was conducted for a duration of 2 months. The purpose of the campaign is to investigate the respondent's willingness to take part in the campaign. At the end of the campaign, the WCO accumulated were recorded and sent to the recycling facilities for disposal. From the results obtained, it can be concluded that majority of the respondents are willing to practice 3R concept. However, the lacked of recycling facilities in the study areas discarded their practice.